Estrés y su afrontamiento en directores y directoras de colegios y escuelas en el circuito 03 de la provincia de Heredia - Pedro Ureña-Bonilla; Carmen Castro-Sancho (Universidad Nacional, Costa Rica, 2004)
The purpose of this study was to analyze how school principals working in the third circuit of the province of Heredia experienced and faced stress. 17 educational managers (11 women and 6 men) participated in the survey. The instruments used allowed us to assess stressing situations, the emotional correlation of each one of the situations, mood profiles and strategies to face them. In general, the findings allowed important factors to be identified as triggers of stress and its accompanying emotions. Some of these factors are: irresponsibility, lack of commitment and of a sense of belonging to the institution, lack of control and lack of respect. The psychological profile basically revealed a group of professionals with good vitality in spite of the burden derived from their positions. Finally, the strategies to cope with stress are mainly rational and denote a group of principals that prefer to plan their actions, to respond according to the problem and to reflect upon the situation.